Pengaruh Etos Kerja Islam Terhadap Prestasi Karyawan Pada PT. BPRS Al-Washliyah - Ayu Safrianti (Universitas Muhammadiyah Sumatera Utara, 2021)
Ayu Safrianti, The Influence of Islamic Work Ethic on Employee Achievement at PT. BPRS Al-Washliyah The purpose of this study is to find out